Developing a hierarchical model based on quality dimensions to enhance business excellence in hotel industry of Bangladesh - Islam, Rafikul; Rahman, Mahbubar; Wan Husain, Wan Rohaida; Mohd. Israil, Khaliq Ahmad (Academy for Global Business Advances (AGBA), 2017)
This study develops a model based on Malcolm Baldrige National Quality Award (MBNQA) that enables ranking of the quality dimensions for achieving business excellence in the hotel industry of Bangladesh. The study adopted a sequential mix method approach. Semi structured interviews with 24 participants were initially conducted to identify the quality dimensions. Subsequently, a questionnaire survey was carried out on 40 respondents to prioritise the identified elements, and 32 respondents were further surveyed to evaluate a selected number of hotels in Bangladesh. Data for all three phases were collected from different stakeholders ranging from policy makers, quality management experts, experienced hotel guests, and top and middle-level hotel executives. Thematic analysis was used during the qualitative stage. Subsequently, the relative measurement of Analytic Hierarchy Process (AHP) and the absolute measurement of AHP were applied in the second and third phases of data collection and analysis. The study uncovered eight criteria namely: top management commitment and leadership, strategic planning, service process management, employee focus, customer/guest focus, quality management, communication, and business results during the qualitative stage together with their corresponding sub-criteria. Hotel Radisson Blu of Chittagong was identified as the best performing hotel among the selected hotels. The study did not stop by developing the model only but it has also shown how this model can be applied in practice. The business excellence model developed for hotel industry can be used by Bangladeshi practitioners to measure performance of hotels. Moreover, the model is generic enough that can be applied to measure performance of hotels in other countries with minor modifications in the model framework.